Characterizing the swimming tumble turn using acceleration data - Slawson, S. E.; Justham, L. M.; Conway, P. P.; Le-Sage, T.; West, A. A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2012)
Work detailed in this paper describes the development of a swimmer-worn, wireless sensor node capable of capturing real time acceleration data during all phases of swimming, i.e. the start, free swimming, and turns. Analysis of results focuses on the interpretation of these data for the tumble turn. Phases of the turn are characterized in the data enabling the contribution of each phase - approach, rotation, and glide - to be evaluated. A single subject, a triathlete, 400 m swim trial was used to capture acceleration data of multiple turns for analysis. Statistical process control (SPC) charts were used to present results and give an indication of whether correlation occurred between each of the turn phases and total turn time. Informal feedback from swimming professionals suggested that these presentation methods supply results in an easy-to-interpret manner, whereby outliers and variations in performance could be visually identified.